Toward a Politics of Immediation - Manning, Erin (Frontiers in Sociology, 2019)
A passage from Fred Moten haunts the writing of these words that seek to push a politics of identity toward a politics of immediation. In a parenthetical aside in a paper on the city and the commune, Fred Moten cautions us as regards the critique of identity politics. Too often, he writes, critiques of identity politics are waged against "non-white, non-straight, non-male identity [...] while courteously leaving politics to its own uncriticized devices” (2016: 163). Through the figure of immediation, I ask: what happens when we do not insert a mediating gesture at the heart of experience? Is such a move capable of problematizing the figure of identity while still remaining sensitive to the fact for some the loss of a sense of identity may feel like the very same gesture as the colonial act of exclusion from the category of the human? In this double articulation of refusing mediation and introducing a time-form that challenges human-centred, colonial history, can we create an affirmative politics of emergent subjectivity that does not ignore that allegiances are necessary in the face of the systemic violence of oppression? The task, it seems to me, involves recasting allegiance such that it need no longer be subsumed to identity, and, by extension, to the individual. For the individual, that pet-figure of neoliberalism, is nothing more than the other side of the subject, which is the other side of the human. To focus on the individual in an exploration of modes of existence, to make the politics about the individual, is to reinstall a mediation that knows in advance how to recognize the human as orienter of experience. The problem of identity must instead be engaged from the perspective of Wynter’s “descriptive statement” of the human. This category of the human, as Wynter underscores, is concerned to perpetuate a genre of the human (2015: 9). What kinds of sociality cut across this genre?